2021
DOI: 10.1186/s12862-021-01950-2
|View full text |Cite
|
Sign up to set email alerts
|

Spatial population genetic structure and colony dynamics in Damaraland mole-rats (Fukomys damarensis) from the southern Kalahari

Abstract: Background Non-random associations within and among groups of social animals can provide valuable insight into the function of group living and the evolution of social behaviour. Damaraland mole-rats (Fukomys damarensis) demonstrate extremely high levels of reproductive skew, and dispersal is considered to be male-biased in onset and frequency, although asymmetry in dispersal distance is yet to be investigated. Dispersal may be positively correlated with increasing favourable environmental cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 87 publications
(119 reference statements)
3
22
0
Order By: Relevance
“…Similar patterns of group formation as in obligate cooperative mammals are seen in many eusocial insect societies (62-65), and various studies have suggested that the fissioning of large groups may also be an important driver of new group formation in the social mole-rats (19,21,31,66). However, research on numerous mole-rat populations also indicates that the dispersal of solitary individuals is widespread (24, 41, 6668), and evidence of individuals living singly in burrow systems has repeatedly been remarked upon (24,68,69). The survival rate of single individuals and the frequency with which these individuals form new breeding groups has not been quantified, but if it represents an important route to breeding, then it would suggest that mole-rats do not need a workforce to reproduce successfully.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…Similar patterns of group formation as in obligate cooperative mammals are seen in many eusocial insect societies (62-65), and various studies have suggested that the fissioning of large groups may also be an important driver of new group formation in the social mole-rats (19,21,31,66). However, research on numerous mole-rat populations also indicates that the dispersal of solitary individuals is widespread (24, 41, 6668), and evidence of individuals living singly in burrow systems has repeatedly been remarked upon (24,68,69). The survival rate of single individuals and the frequency with which these individuals form new breeding groups has not been quantified, but if it represents an important route to breeding, then it would suggest that mole-rats do not need a workforce to reproduce successfully.…”
Section: Introductionmentioning
confidence: 65%
“…New groups typically form and successfully breed when coalitions of individuals disperse and settle together (52,53), when large groups fission into smaller, distinct breeding units (54)(55)(56)(57), or when a breeding territory including helpers is inherited by existing group members (58)(59)(60)(61). Similar patterns of group formation as in obligate cooperative mammals are seen in many eusocial insect societies (62)(63)(64)(65), and various studies have suggested that the fissioning of large groups may also be an important driver of new group formation in the social mole-rats (19,21,31,66). However, research on numerous mole-rat populations also indicates that the dispersal of solitary individuals is widespread (24,41,(66)(67)(68), and evidence of individuals living singly in burrow systems has repeatedly been remarked upon (24,68,69).…”
Section: Introductionmentioning
confidence: 72%
“…Thus offspring of either sex must disperse from the natal group to acquire reproductive opportunities, even though strong ecological constraints make successful settlement rare. Indeed, very few individuals within a Damaraland mole-rat populations breed at some point in their lives (<8%; Jarvis and Bennett, 1993;Torrents-Ticó et al, 2018;Mynhardt et al, 2021;Thorley et al, 2021). Previous field studies of social mole-rats have shown that when individuals disperse, they frequently do so alone and rarely in coalitions (Jarvis and Bennett, 1993;Torrents-Ticó et al, 2018), and evidence suggests that dispersal occurs both above and below ground (Hazell et al, 2000;Bray et al, 2012;Patzenhauerová et al, 2013;Finn, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Rainfall and soil moisture also affect the ability of Damaraland mole-rats to leave their natal colony, disperse and join other colonies or form new colonies. High rainfall results in an increase in the number of small colonies and a decrease of large colonies in an area likely due to non-breeding individuals leaving their colonies [ 29 , 30 ]. Interestingly, males disperse more often and over longer distances than females and are more likely to join an established colony whereas females split off from a colony to start a new one [ 26 , 29 ].…”
mentioning
confidence: 99%
“…High rainfall results in an increase in the number of small colonies and a decrease of large colonies in an area likely due to non-breeding individuals leaving their colonies [ 29 , 30 ]. Interestingly, males disperse more often and over longer distances than females and are more likely to join an established colony whereas females split off from a colony to start a new one [ 26 , 29 ]. Seasonal differences can also be seen in the reproductive activity and hormone concentrations of subordinate individuals.…”
mentioning
confidence: 99%